2017
DOI: 10.1007/s00590-017-2080-z
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein levels for early detection of early postoperative complications after proximal femoral fracture surgery

Abstract: Prospective observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Their 42 patients included hip arthroplasties as well as osteosynthetic treatments. The inclusion of osteosyntheses could have possibly influenced their analysis, while their overall number of patients was lower than ours [49]. Klim et al similarly investigated the predictive value of CRP kinetics in the detection of a PJI in total hip or knee arthroplasties.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Their 42 patients included hip arthroplasties as well as osteosynthetic treatments. The inclusion of osteosyntheses could have possibly influenced their analysis, while their overall number of patients was lower than ours [49]. Klim et al similarly investigated the predictive value of CRP kinetics in the detection of a PJI in total hip or knee arthroplasties.…”
Section: Discussionmentioning
confidence: 79%
“…In comparison to our study the authors examined a higher number of patients with infection. Schutz et al [49] achieved a sensitivity of 65% and a specificity of 85% with two CRP values above their correlation, which was calculated with the help of a linear mixed model. Their 42 patients included hip arthroplasties as well as osteosynthetic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Kinoshita et al utilized Hgb and C-reactive protein (CRP) levels to track the post-operative course of a patient who developed a profunda femoris artery pseudoaneurysm after internal fixation of a trochanteric fracture [8] . While rising CRP levels are used to detect early signs of post-operative infections, Kinoshita et al observed rising CRP levels with the development of their patient's anemia in the absence of infection, which all normalized after blood transfusions and embolization [8] , [10] . Notably, our patient experienced significant intra-operative bleeding for a short period during surgery, but it was the hemodynamic decompensation and precipitous drop in Hgb post-operatively that prompted further workup.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, rising CRP levels were also observed with the progression of anemia without signs of infection of the surgical wounds or other organs. CRP levels for early detection are said to correlate with early postoperative complications such as infection, dislocation, and hematoma after proximal femoral fracture surgery [ 11 ]. It should be noted that not only infection can develop but also vascular injury, swelling of the affected limb, decreased Hb levels, and elevated CRP levels in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%